If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.6(y + 4) = 1.2 Reorder the terms: 0.6(4 + y) = 1.2 (4 * 0.6 + y * 0.6) = 1.2 (2.4 + 0.6y) = 1.2 Solving 2.4 + 0.6y = 1.2 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2.4' to each side of the equation. 2.4 + -2.4 + 0.6y = 1.2 + -2.4 Combine like terms: 2.4 + -2.4 = 0.0 0.0 + 0.6y = 1.2 + -2.4 0.6y = 1.2 + -2.4 Combine like terms: 1.2 + -2.4 = -1.2 0.6y = -1.2 Divide each side by '0.6'. y = -2 Simplifying y = -2
| -5x+7y=11 | | 7x+29x=180 | | 1+8=48+x | | 7x=29x | | 6.07*5.3= | | 2y+18=12-6(1y+7) | | 2x-1=10x-89 | | 5x+5=86-4x | | x^2+10x+25=12 | | 6.04*5.07= | | 6-8x=121-43x | | 3w^2=17w+6 | | 11x+7=7x+18 | | 145-6x=21x+19 | | 3x-1=11x-97 | | 5x+43=8x+10 | | 160-6x=5x+6 | | 6x+9=5x+18 | | 5-8x=195-43x | | 5x+28=14x-53 | | -34-5x=6-9x | | -56-9x=9x+16 | | -15-7w+2w^2=0 | | 6x+12=-92-7x | | -132-7x=19x+21 | | 2w^2=7w+15 | | 4x+8=-118-10x | | 58-6x=7x+19 | | 66-3x=9x+18 | | 6x-3=14x-62 | | 3x+5=40-2x | | 12x-11=9x+4 |